Public health expenditure, governance and health outcomes in Malaysia - Riayati Ahmad,; Junaidah Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
According to the World Health Organization (WHO), government plays a crucial role in providing quality life for its citizens through good health system. There has been less attention given in analysing the relationship between government expenditure, governance and health outcomes particularly in developing countries. This paper aims to study the impact of public health expenditure and governance on health outcomes in Malaysia. An Autoregressive Distributed Lag (ARDL) cointegration framework has been used to analyse data from 1984 to 2009. The results based on the bounds testing procedure show that a stable, long-run relationship exists between health outcomes and their determinants; namely income level, public health expenditure, corruption and government stability. The results also reveal that public health expenditure and corruption affect long- and short run health outcomes in Malaysia. The findings are important to the policy makers in making decisions to improve the citizens’ quality of life. We suggest the Ministry of Health of Malaysia to conduct more consultations with other ministries and other stakeholders in health services as to identify the needs and emphasize on the importance of health program to the society. At the same time, attention should be given to reduce or eliminate the corruption rate as it has adverse effects on the country.